2018
DOI: 10.1093/infdis/jix625
|View full text |Cite
|
Sign up to set email alerts
|

High Turnover of Tissue Macrophages Contributes to Tuberculosis Reactivation in Simian Immunodeficiency Virus-Infected Rhesus Macaques

Abstract: Results suggest that SIV-related damage to macrophages contributes to Mtb reactivation during coinfection. This also supports strategies to target lung macrophages for the treatment of TB.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
64
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
3
1

Relationship

5
4

Authors

Journals

citations
Cited by 46 publications
(65 citation statements)
references
References 24 publications
1
64
0
Order By: Relevance
“…The frequency of myeloid subpopulations increased in BAL was generally reduced in blood (Fig S13e-h), with two exceptions - pDCs and CD14 + CD16 + monocytes, which were increased in the blood as well as BAL (Fig S13g-h). Relative to AMs, IMs have a shorter half-life, exhibit continuous turnover, and may help to maintain homeostasis and protect against continuous pathogen exposure from the environment 14 . Increased recruitment of pDCs to the lungs suggests a potentially important feature of protection from advanced COVID-19 disease in the rhesus macaque model since they are a major source of anti-viral Type I interferons such as IFN- α , the levels of which were elevated in the BAL within 1-3 dpi (Fig 3b).…”
Section: Mainmentioning
confidence: 99%
“…The frequency of myeloid subpopulations increased in BAL was generally reduced in blood (Fig S13e-h), with two exceptions - pDCs and CD14 + CD16 + monocytes, which were increased in the blood as well as BAL (Fig S13g-h). Relative to AMs, IMs have a shorter half-life, exhibit continuous turnover, and may help to maintain homeostasis and protect against continuous pathogen exposure from the environment 14 . Increased recruitment of pDCs to the lungs suggests a potentially important feature of protection from advanced COVID-19 disease in the rhesus macaque model since they are a major source of anti-viral Type I interferons such as IFN- α , the levels of which were elevated in the BAL within 1-3 dpi (Fig 3b).…”
Section: Mainmentioning
confidence: 99%
“…Since most of the CCR6+ CD4 T cells in BAL were also positive for CXCR3 (Figure 7) , we used CXCR3 as a proxy for both chemokine receptors (Figure 8). We also stained lung sections with antibodies to CD163 and CD68 to identify macrophages(32). Immunostaining of lung sections from animals with asymptomatic LTBI showed that CXCR3+ CD4 T cells were present in lung tissue (Figure 8A) , with higher densities of CXCR3+ CD4 T cells in granulomatous areas of the lung compared to non-granulomatous areas ( Figure 8B ).…”
Section: Resultsmentioning
confidence: 99%
“…Procedures for weekly complete blood counts (CBC), chemistry, chest radiographs (CXR) and BAL at week 3 and every four weeks thereafter have been described previously (19, 24, 32, 66). CXRs were scored by veterinary clinicians in a blinded fashion on a subjective scale of 0–4, with a score of 0 denoting normal lung and a score of 4 denoting severe tuberculous pneumonia, as previously described (19).…”
Section: Methodsmentioning
confidence: 99%
“…NHP has been an invaluable in vivo model to better understand the role of macrophages in SIV/HIV pathogenesis (Merino et al, 2017). Considering Siglec-1 binds sialylated lipids present in the envelop of HIV-1 and SIV (Izquierdo-Useros et al, 2012a;Puryear et al, 2012), we examined the presence of Siglec-1 positive alveolar macrophages in lung biopsies obtained from different NHP groups: (i) co-infected with Mtb (active or latent TB) and SIV, (ii) monoinfected with Mtb (active or latent TB), (iii) mono-infected with SIV, and (iv) healthy (Table S1, Figure S2A) (Cai et al, 2015;Kuroda et al, 2018;Souriant et al, 2019). Histological immunostaining confirmed the presence of Siglec-1 + alveolar macrophages in the lungs of healthy NHP , and revealed its significant increase in NHP mono-infected with either Mtb or SIV .…”
Section: Siglec-1 + Alveolar Macrophage Abundance Correlates With Patmentioning
confidence: 99%